Neustonic distribution of decapod planktonic stages and competence of brachyuran megalopae in coastal waters - Moreira, Fabiana T.; Harari, Joseph; Flores, Augusto A. V. (CSIRO Publishing, 2007)
Settlement rate may not reflect larval supply to coastal waters in different marine invertebrates and demersal fishes. The importance of near-shore oceanography and behaviour of late larval stages may be underestimated. The present study conducted neustonic sampling over station grids and along full-length transects at two embayments in south-eastern Brazil to (1) compare diurnal and nocturnal occurrence of most frequent decapod stages to assess their vertical movements, (2) describe the formation of larval patches and (3) measure competence of crab megalopae according to their distance to recruitment grounds. Several shrimp species apparently undergo a diel vertical migration, swimming crab megalopae showed no vertical movements and megalopae of the intertidal crab Pachygrapsus transversus revealed a reversed vertical migration. During the day, crab megalopae aggregated in convergence zones just below surface slicks. These larvae consisted of advanced, pre-moult stages, at both mid-bay and near-shore patches. Competence, measured as the time to metamorphosis in captivity, was similar between larval patches within each taxon. Yet, subtidal portunids moulted faster to juveniles than intertidal grapsids, possibly because they were closer to settlement grounds. Megalopae of Pachygrapsus from benthic collectors moulted faster than those from bay areas. These results suggest that alternative vertical migration patterns of late megalopae favour onshore transport, and actual competence takes place very close to suitable substrates, where larvae may remain for days before settlement. Lack of correlation between larval supply and settlement for Pachygrapsus suggests that biological processes, besides onshore transport, may play an important role in determining settlement success of coastal crabs.
Keywords: larval supply; settlement; vertical migration